Functional and structural insight into properdin control of complement alternative pathway amplification. (6th March 2017) - Pedersen, Dennis V; Roumenina, Lubka; Jensen, Rasmus K; Gadeberg, Trine AF; Marinozzi, Chiara; Picard, Capucine; Rybkine, Tania; Thiel, Steffen; Sørensen, Uffe BS; Stover, Cordula; Fremeaux‐Bacchi, Veronique; Andersen, Gregers R
Abstract: Properdin (FP) is an essential positive regulator of the complement alternative pathway (AP) providing stabilization of the C3 and C5 convertases, but its oligomeric nature challenges structural analysis. We describe here a novel FP deficiency (E244K) caused by a single point mutation which results in a very low level of AP activity. Recombinant FP E244K is monomeric, fails to support bacteriolysis, and binds weakly to C3 products. We compare this to a monomeric unit excised from oligomeric FP, which is also dysfunctional in bacteriolysis but binds the AP proconvertase, C3 convertase, C3 products and partially stabilizes the convertase. The crystal structure of such a FP‐convertase complex suggests that the major contact between FP and the AP convertase is mediated by a single FP thrombospondin repeat and a small region in C3b. Small angle X‐ray scattering indicates that FP E244K is trapped in a compact conformation preventing its oligomerization. Our studies demonstrate an essential role of FP oligomerization in vivo while our monomers enable detailed structural insight paving the way for novel modulators of complement. Synopsis: Functional studies of oligomeric and two different monomeric forms of the complement regulator FP demonstrate an essential role of oligomerization, while structural studies suggest that the contact between FP and the alternative pathway convertase is mainly mediated by a single FP thrombospondin repeat and a small region in C3b. The point mutation E244K prevents FP oligomerization in vivo giving rise to low activity in the alternative pathway of complement. Biophysical measurements and functional assays show that FP oligomerization results in much tighter interactions with C3‐opsonized surfaces and is required for efficient stabilization of convertases. The crystal structure of FP bound to the SCIN stabilized AP C3 convertase reveals the outline of monomeric FP and identifies the C3b C345c domain as the dominant interaction partner in the convertase. The FP E244K variant adopts a compact monomeric conformation as compared to a monomer excised from oligomeric FP. Abstract : Characterization of a new patient mutation in the complement system regulator properdin shows that its oligomerization is essential for activation of the alternative pathway and bacteriolysis.